Age-specific Features of a Cardiorespiratory Response to the Combined Action of Hypoxia and Hypercapnia - N. A. Agadzhanyan; V. G. Dvoyenosov (Общая реаниматология)
A re-entry breathing test has established that progressive hypoxia and hypercapnia cause inhibited gas exchange that are more pronounced in groups of young athletes and schoolchildren. In adult athletes, higher cardiorespiratory resistance is provided by oxygen utilization and the maintenance of the required level of blood flow.